2020
DOI: 10.1039/d0tb01546f
|View full text |Cite
|
Sign up to set email alerts
|

Tuneable peptide cross-linked nanogels for enzyme-triggered protein delivery

Abstract: A tuneable peptide-crosslinked, temperature-sensitive nanogel platform for protein delivery in response to MMP-7, which is overexpressed in many pathologies, is presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…The LCST can be tuned by adjusting the polymer component. The LCSTs of PNIPAM and PNCPAM are 32 and 49 °C, respectively 36 . P(NIPAM‐ co ‐NCPAM) obtained by copolymerization of NIPAM and NCPAM had an LCST ranging from 32 to 49 °C with the varied ratio of NIPAM and NCPAM.…”
Section: Thermoresponsive Nanogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LCST can be tuned by adjusting the polymer component. The LCSTs of PNIPAM and PNCPAM are 32 and 49 °C, respectively 36 . P(NIPAM‐ co ‐NCPAM) obtained by copolymerization of NIPAM and NCPAM had an LCST ranging from 32 to 49 °C with the varied ratio of NIPAM and NCPAM.…”
Section: Thermoresponsive Nanogelsmentioning
confidence: 99%
“…Massi et al . synthesized P(NIPAM‐ co ‐NCPAM) with different monomer ratios and examined their physical properties 36 . The higher molar ratio of NIPAM and NCPAM, the higher phase transition temperature.…”
Section: Thermoresponsive Nanogelsmentioning
confidence: 99%
“…These nanogels were highly dependent on glucose or pH concentrations, where low amounts of proteins were released in physiological pH or under healthy blood glucose level, while the rapid release was seen at lower pH or under diabetic blood glucose level [83]. Massi et al generated a temperature-sensitive nanogel that responded to matrix metalloproteinase-7 (MMP-7) and with the addition of N-cyclopropylacrylamide (NCPAM) into NIPAM-based copolymer, it allowed the encapsulation of protein cargo and nanogel-crosslinking at slightly elevated temperatures [84].…”
Section: Delivery Of Peptides or Proteins Using Stimuli-responsive Hydrogelsmentioning
confidence: 99%
“…Most recently, CC-9 peptide conjugated to poly(acrylamide-co-methacrylic acid) nanogels showed enhanced co-localization with SW-48 colon cancer cell lines to augment colon cancer targeting abilities [103]. To date, various peptides (e.g., papain, albumin, arginine-glycine-aspartic acid (RGD), and azido-bi-functionalized peptides) have been used in the development of peptide-polymer conjugates [101,[104][105][106]. Studies reported that these peptide-polymer NPs provides new opportunities to generate hybrid NPs with attractive properties such as tumor targeting, stimuli-and microenvironmental responsiveness while minimizing off-target toxicity [101,104].…”
Section: Peptide-polymer Conjugatesmentioning
confidence: 99%